Therapy with Fetal Neuronal Cells in Acute Period of Experimental Ischemic Stroke (Antioxidative Effect) - Lebedinets, D. V.; Ovsyannikov, S. Ye.; Lebedinets, V. V.; Ostankov, M. V.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2010)
In this research there are presented the results of the effect of cryopreserved fetal neuronal cells (cFNCs) on the dynamics of neurological deficit and state of the processes of lipid peroxidation (LPO) in an acute period of brain ischemia in white rats. It has been shown that the introduction of cFNCs corrected the impairment of LPO activity, reduced the level of free radical metabolites in brain substance, liver and blood serum, strengthened endogenous antioxidant protection, improved clinical status of rats and increased the viability index of the animals. The carried-out studies revealed statistically significant effect of introduced intraperitoneally cFNCs in an acute period of experimental brain ischemia of laboratory animals. The findings enable the considering of the application of cFNCs in a combined treatment of ischemic impairments of brain blood circulation as perspective one.